"Economic dimensions of the Sardar Sarovar project / by Alag, Y. K....[ et al]" - "Desai, R . D ; Guha, G .S ; Kashyap, S . P." (New Delhi, 1995)
This book contains an updated economic analysis of the Sardar Sarovar Project using "real" costs and benefits. These have been estimated at three different levels of irrigation efficiency and two different assumptions on availability of Municipal and Industrial water. Based on a computerised model, the book provides alternate "internal rates of return" for each of these different scenarios. The Authors argue that the acceptibility of such a project is enhanced by the fact that the economic returns calculated are washed off all financial noise whereas inflation is in favour of minimising wasteful expenditure as against.
Keywords: Sardar sarovar project economic aspects